Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Dalam Pelajaran Hukum Tajwid - 'Aini, Athiyyah Fudlla (MULTINETICS, 2021)
Indonesia is a country with a majority muslim population. So that the science of religion needs to be taught from an early age, for example is the science of Tajweed.  Recently, the development of technology in Indonesia has been very fast, but interactive religious learning using electronic media is currently still few especially interactive learning media with the theme of Tajweed learning.  For this reason, the author has a goal to develop a legal learning media application for Tajweed to make it easier for children and parents to learn (hukum tajwid) wherever and whenever. In this learning media, distribution efforts are made by making an application that can be installed on an Android smartphone. So that it is easier to access and use by the community. In addition, research is carried out on the success of this learning media through 2 aspects, namely aspects of the attractiveness and quality of learning media which are assessed by experts in the field of animation/learning media, as well as aspects of the quality of the content of learning media judged by the community.  The approach in this research is quantitative with descriptive research type. The method used in this research is a survei method using a questionnaire technique.  Respondents in this study were 4 expert respondents and 40 community members, which were obtained from distributing online questionnaires. The results of this study show that the attitudes of 4 expert respondents regarding this Learning Media are 81 %% and are in the "Very Good" category and the attitudes of 40 general public respondents are 93.7% and are in the "Very Good" category.